Women and African Traditional Religion - Idumwonyi, Itohan Mercy; Eduviere, Osamamen Oba (The Palgrave Handbook of African Women's Studies, 2020)
Studies reveal that religions with the image of a male god give its male members the cultural-religious currency of power. African Traditional Religions (ATR) may have female goddesses, but it is patterned after the male image of the Supreme Being. ATR, like Abrahamic religions, is a masculine-based and patriarchal religion, promoting subordination in ways that women mostly play peripheral roles in religious spheres. Although women perform religious duties as diviners, herbal doctors, priests, and mystics, they, however, do so in lesser degrees compared to the men. Also, spirit possession is common for women because of their relegated status. ATR’s key players sanction relegation for females and female worshippers. What factors enable gender politics? Besides, what are the attendant implications of gender exclusion in ATR? This chapter draws inference on gender, religious studies, and anthropological theories, with particular reference to gender politics. It focuses on women and advances an argument against the masculinization at play in ATR. It argues that ATR’s masculinization project impacts gender relations and points to the disparity in the status of women and men within the tradition and society. It further analyzes the nature of power and how symbols, myths, and culture have become tools for politicizing gender relations in ways to short-change women. It concludes with the effect of social-cultural constructions and the invaluable gains in pursuing inclusivity that does not marginalize the Other. It further suggests potential transformation with hopes that it will stimulate critical reflections on this subject.
free
Keywords: Africa; African Traditional Religion; Cosmological myths; Gender exclusion; Gender politics; Inclusivity; Menstrual blood; Patriarchy; Rituals and women participation